The efficiency of macrophytes for heavy metals removal from water - Materac, Milena; Sobiecka, Elżbieta (Biotechnology and Food Science, 2017)
Nowadays heavy metals pollution has become one of the most serious environmental problems. Advances in science and technology are leading to the degradation and contamination of aquatic environments. Pollution in aquatic ecosystems poses a serious threat to aquatic biodiversity and serves health hazards in humans. The traditional methods of the environment cleaning in practice are expensive and non-eco friendly can lead to the secondary pollution. It is a reason why the aquatic plants (macrophytes) as the biological remediation methods have been used. Macrophytes play an important role in the biological methods of the water remediation because they have capability to improve the quality of water by absorbing heavy metals with their leaves and effective root systems. This review discusses the potential of different aquatic plants (macrophytes) in purifying water and wastewater.